2015
DOI: 10.1111/jcpe.12393
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic effect to treat residual pockets in periodontal patients: a randomized controlled clinical trial

Abstract: Within the limits of this clinical trial and considering the laser and photosensitizer protocol used, PDT failed to demonstrate additional clinical and bacteriological benefits in residual pockets treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 38 publications
7
69
1
2
Order By: Relevance
“…A recent parallel‐group study published by Carvalho et al. () yielded a similar result for T. denticola . Further studies are needed to establish the most adequate treatment modality for the destruction of these bacteria.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A recent parallel‐group study published by Carvalho et al. () yielded a similar result for T. denticola . Further studies are needed to establish the most adequate treatment modality for the destruction of these bacteria.…”
Section: Discussionsupporting
confidence: 62%
“…However, there is no agreement to date on the benefits of PDT as a coadjuvant to SRP. Although there are descriptions of additional improvements in clinical parameters such as probing depth, clinical attachment level and bleeding on probing (Alwaeli, Al‐Khateeb, & Al‐Sadi, ; Betsy, Prasanth, Baiju, Prasanthila, & Subhash, ; Braun, Dehn, Krause, & Jepsen, ; Campos et al., ; Franco et al., ; Lulic et al., ), other authors have reported no difference resulting from the addition of PDT (Carvalho et al., ; Dilsiz, Canakci, & Aydin, ; Pourabbas et al., ; Theodoro et al., ; Yilmaz et al., ). Overall, most studies have failed to show additional microbiological benefits using PDT as a coadjuvant treatment (Carvalho et al., ; Christodoulides et al., ; Gómez, Domínguez, García‐Kass, & García‐Núñez, ; Yilmaz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…showed that PDT also eliminates P. gingivalis and deactivates the pro‐inflammatory cytokines TNF‐α and IL‐1β . Carvalho investigated the efficiency of PDT with a diode laser with a wavelength of 660 nm in 34 patients with residual pockets after initial treatment . The results showed no significant differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial photodynamic therapy (aPDT) is becoming an effective method of antibacterial treatment and may be used as adjunct therapy for the treatment of severe periodontitis (de Oliveira, Schwartz‐Filho, Novaes, & Taba, ). aPDT has been evaluated in in vitro and in vivo studies (Betsy, Prasanth, Baiju, Prasanthila, & Subhash, ; Carvalho et al., ; Chondros et al., ; Komerik, Wilson, & Poole, ; Komerik et al., ; Moreira et al., ; de Oliveira, Novaes, Taba, de Souza, & Papalexiou, ; Qin, Luan, Bi, Sheng, et al., ; Ramos et al., ; Sarkar & Wilson, ). This therapy presents the principle of eliminating cells through the use of a photosensitizing agent (optical absorption‐dye) and a light source (low‐intensity laser with the appropriate wavelength).…”
Section: Introductionmentioning
confidence: 99%